Kondisi pH, Suhu, dan Kadar Air pada Tahap Pengomposan Tandan Kosong Sawit - Azzah Fizda; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Composting ia a simple and low cost method for reduce a waste to be aeco-friendly product. In composting process, pH, temperature, and moisturecontent conditions must be available for the success of the composting. pH,temperature, and moisture content conditions is a main factor that affected thecomposting process. This research aim to learn pH, temperature, and moisturecontent conditions during composting in both variation of empty fruit bunch(EFB). Variations of raw material are EFB without pretreatment and EFBpretreatment by C. comatus fungi. Both of variations is adding anaerobic sludgewith ratio EFB : anaerobic sludge is (1:3). Result of this research shows the bestvariation is EFB pretreatment by C. comatus fungi. This variation reach C/Nratio 18 with 7 days composting period. Temperature in composting this variationaround (28,6 -38)˚C, pH around (7,6 – 7,98), and moisture content around 90%.Keywords : EFB, Composting, pH, Temperature, Moisture Content, C. comatus,C/N ratio, Composting Period